2018
DOI: 10.3390/antibiotics7020038
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prescribing for Oro-Facial Infections in the Paediatric Outpatient: A Review

Abstract: There are many reports on the complications associated with antibiotics abuse during the treatment of paediatric patients, particularly those related to antimicrobial resistance. The dental profession is no exception; there is growing evidence that dental practitioners are misusing antibiotics in the treatment of their paediatric patients. This review is directed to dental practitioners who provide oral healthcare to children. It is also directed to medical practitioners, particularly those working in emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 70 publications
(84 reference statements)
0
34
0
3
Order By: Relevance
“…Most of these infections are bacterial infections originating in the dental pulp, and less frequently in the periodontal, and salivary tissues. Operative intervention in the form of dental fillings, root canal treatment, scaling, root planning, extraction or abscess drainage is considered the gold standard for treatment [3].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these infections are bacterial infections originating in the dental pulp, and less frequently in the periodontal, and salivary tissues. Operative intervention in the form of dental fillings, root canal treatment, scaling, root planning, extraction or abscess drainage is considered the gold standard for treatment [3].…”
Section: Introductionmentioning
confidence: 99%
“…Penicillin administration has also recommended and showed better in vitro activity as compared to other antibiotics including clindamycin [32]. In the case of periodontitis, the sole prescription of penicillin is not a frequent therapeutic scheme; however, it is frequently prescribed in orofacial infections [33,34]. As this case showed, removal of the affected tissues and proper debridement resulted in an adequate healing response.…”
Section: Discussionmentioning
confidence: 88%
“…Among dentists, there is a lack of consensus about antibiotic prescription (Khouly et al, 2019); in addition, one of the most recent reviews on the use of antibiotics in dentistry (Marchionni et al, 2017) has pointed out that for simple tooth extractions the use of antibiotics could increase the risks of the medication's adverse effects without significantly preventing postoperative complications. Above all, it turned out that dentists frequently prescribed antibiotics in medically compromised patients, who—according to the current guidelines—no longer need antibiotic prophylaxis (Colterjohn, Beer, Petruccelli, Zabtia, & Winemaker, 2014; Dar‐Odeh, Fadel, Abu‐Hammad, Abdeljawad, & Abu‐Hammad, 2018; Dayer et al, 2013; Khouly et al, 2019). What is even more peculiar is that some authors identified non‐clinical factors—such as pressure from the patient or the family physician—that could influence the dentists in prescribing antibiotics (Dayer et al, 2013; Soheilipour et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…What is even more peculiar is that some authors identified non‐clinical factors—such as pressure from the patient or the family physician—that could influence the dentists in prescribing antibiotics (Dayer et al, 2013; Soheilipour et al, 2011). This underlined not only inadequate knowledge among dentists, but also an insufficient awareness or a slow adherence to the guidelines among physicians (Dar‐Odeh et al, 2018; Habib et al, 2015).…”
Section: Discussionmentioning
confidence: 99%